The Integration of Dhikr and Reflection as a Coping Strategy for Managing Anxiety Symptoms - Ma’rufah, Qurrotul Ahsani; Ridho, Moch Taufiq (West Science Islamic Studies, 2026)
The prevalence of anxiety symptoms among modern individuals continues to rise due to psychological pressure, social expectations, and the increasing complexity of daily life. This condition demands coping strategies that address not only rational-cognitive aspects but also the spiritual dimension of human experience. This study examines the integration of dhikr (remembrance) and fikir (reflective thinking) as a holistic coping mechanism for managing anxiety symptoms. Employing a library research method, this study reviews psychological literature, Islamic scholarship, and empirical studies related to coping mechanisms. The findings indicate that dhikr functions as an emotional regulator that reduces physiological arousal associated with anxiety, while dhikr facilitates more adaptive cognitive appraisal of stressors. The synergy between these practices fosters inner tranquility and strengthens cognitive regulation, thus enhancing individual resilience against anxiety. This study highlights the relevance of spiritual-cognitive approaches as complementary strategies within contemporary psychological interventions.